STRATEGI PEMURIDAN BAGI NARAPIDANA DI LP CIPINANG JAKARTA TIMUR BERDASAR PADA 2 TIMOTIUS 4:2 DAN RELEVANSINYA BAGI PELAYANAN MISI KAUM MARGINAL - Matheus Mangentang; Malik Bambangan; Dyulius Thomas Bilo; Moses Wibowo (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
Everyone believe is called to be a disciple by Christ. Christianity without discipleship is Christianity without Christ. Departing from this statement, it is understood that, only by becoming a disciple of Christ can one become a light or witness of Christ in the world and lead others to Christ. The true Christian life, is not meant to simply accept Jesus as Savior, attend church services, read the Bible, pray, talk about Jesus, but also is intended to represent God and demonstrate the lifestyle of God's kingdom on earth. So true Christians are disciples of Jesus Christ. Because of the importance of that discipleship, students are mentioned 269 times in the New Testament, which refers to individuals who are jointly committed to following Jesus Christ. The purpose of this research is to provide discipleship services for Christian prisoners at Lembaga Pemasyarakatan Cipinang Jakarta Timur. As a result of this research that after this discipleship was held Christian convicts at Lembaga Pemasyarakatan Cipinang Jakarta Timur had a Christlike character, had hope in Christ, could multiply discipleship.